Genotoxicity of Cytolethal Distending Toxin (CDT) on Isogenic Human Colorectal Cell Lines: Potential Promoting Effects for Colorectal Carcinogenesis - Graillot, Vanessa; Dormoy, Inge; Dupuy, Jacques; Shay, Jerry W.; Huc, Laurence; Mirey, Gladys; Vignard, Julien (Frontiers in Cellular and Infection Microbiology, 2016)
The composition of the human microbiota influences tumorigenesis, notably in colorectal cancer (CRC). Pathogenic Escherichia coli possesses a variety of virulent factors, among them the Cytolethal Distending Toxin (CDT). CDT displays dual DNase and phosphatase activities and induces DNA double strand breaks, cell cycle arrest and apoptosis in a broad range of mammalian cells. As CDT could promote malignant transformation, we investigated the cellular outcomes induced by acute and chronic exposures to E. coli CDT in normal human colon epithelial cells (HCECs). Moreover, we conducted a comparative study between isogenic derivatives cell lines of the normal HCECs in order to mimic the mutation of three major genes found in CRC genetic models: APC, KRAS, and TP53. Our results demonstrate that APC and p53 deficient cells showed impaired DNA damage response after CDT exposure, whereas HCECs expressing oncogenic KRASV12 were more resistant to CDT. Compared to normal HCECs, the precancerous derivatives exhibit hallmarks of malignant transformation after a chronic exposure to CDT. HCECs defective in APC and p53 showed enhanced anchorage independent growth and genetic instability, assessed by the micronucleus formation assay. In contrast, the ability to grow independently of anchorage was not impacted by CDT chronic exposure in KRASV12 HCECs, but micronucleus formation is dramatically increased. Thus, CDT does not initiate CRC by itself, but may have promoting effects in premalignant HCECs, involving different mechanisms in function of the genetic alterations associated to CRC.